Clinical characteristics and outcomes of patients with diabetic ketoacidosis of different severity. Issue 45 (6th November 2020) - Wei, Ying; Wu, Chushan; Su, Feiya; Zhang, Han; Zhang, Jinxia; Zheng, Rongxiu
Abstract : Abstract: To analyze the influencing factors and outcomes of the different severity of diabetic ketoacidosis (DKA). A total of 50 children with DKA admitted to the Department of Pediatrics, Tianjin Medical University General Hospital from January 2009 to December 2018 were included in this study. The patients were divided into mild group, moderate group, and severe group according to the severity of the disease. We then analyzed the clinical characteristics and outcomes of the 3 groups. Compared to mild and moderate DKA groups, patients with severe DKA were more likely to present chest tightness, and higher levels of blood osmotic pressure, urea, and creatinine ( P  < .05). Logistic regression analysis showed that blood osmotic pressure, creatinine, and chest tightness were independent factors for severity of DKA. There was a significant difference in the resolution time of DKA among the 3 groups (mild vs moderate: 9.0 hours vs 15.25 hours; moderate vs severe: 15.25 hours vs 24.5 hours, P  < .001). There were statistical differences in the decline of Glasgow score among 3 groups ( P  = .004). Patients with severe DKA showed higher osmotic pressure and creatinine, as well as dyspnea. The children with severe DKA were more likely to present progression of neurological symptoms, which was necessary to pay attention to the presence of brain edema.